The Vegetable Oil as an Alternative Fuel for Diesel Motors - Dimas Noor Ardianto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2023)
It is estimated that fossil fuels will run out if they are exploited on a large scale. In today's developments, there are many vehicle innovations that use diesel fuel. This dependency can be overcome with bio diesel. Various wastes resulting from the processing of agricultural materials have great potential to be processed into alternative fuels to replace coal and fuel oil. These alternative fuels include bioethanol, biodiesel, biogas and biobriquettes. In this research we discuss biodiesel, biodiesel is an alternative fuel which is usually made from agricultural plants such as oil palm. However, this fuel usually cannot be pure oil, usually mixed with diesel. This mixed fuel has not been proven to be good for use in vehicles in the sense that this fuel might affect the torque of the vehicle. In this research we will test which mixture is the best or closest to fossil fuel.